Prestasi Kehalifaan Turki Utsmani di Turki (1299-1922) - ningtyas, mufida putri (Maliki Interdisciplinary Journal, 2025)
Kekhalifaan Turki Utsmani (1299-1922) was one of the largest Islamic empires, exerting significant influence across various aspects, including politics, military, economy, arts, science, and religion. This study examines the achievements and contributions Turki Utsmani in shaping Islamic civilization, as well as the factors leading to its decline. Using a historical and descriptive analytical approach, the study finds that the empire’s golden era was supported by a strong governance system, advanced military strategies, and progress in economic and cultural fields. However, over time, internal and external challenges—such as administrative weaknesses, Western cultural influence, and a decline in scientific innovation—led to the empire’s downfall. The findings highlight that the Ottoman legacy continues to impact the modern Islamic world, particularly in Islamic law, architectural heritage, and geopolitical policies. Therefore, further research on the governance and economic policies of the Ottoman Empire can provide valuable insights for contemporary Islamic civilization.